PENEKANAN HAYATI PENYAKIT MOLER PADA BAWANG MERAH DENGAN TRICHODERMA HARZIANUM, TRICHODERMA KONINGII, DAN PSEUDOMONAS FLUORESCENS P60 - Suprapto Edy Santoso, Loekas Soesanto, dan Totok Agung Dwi Haryanto . (Universitas Lampung, 2007)
Biological Suppression of Moler Disease on Shallot by Trichoderma harzianum, Trichoderma koningii, and Pseudomonas fluorescens P60. Research aiming for (1) knowing efectivity of biological suppression with T. harzianum, T. koningii, and P. fluorescens P60 and (2) studying growth and production of shallot caused by the suppression carried out at the shallot farm. Split-Split Plot Design arranged in Randomized Completely Block Design was used with three replicates. The research result showed that P. fluorescens P60 was the most effective antagonistic agent to suppress the disease either alone or in combination while T. harzianumi and T. koningii did not suppress effectively. Pseudomonas fluorescens P60 could suppress the disease up to 41.96%. The best method of P. fluorescens P60 application was spraying method for 10 mL with 107 cfu/mL population density, which was able to dicrease incubation period, disease intensity, and final pathogen population up to 62.46, 18.19, and 80.67%, respectively. Growth and production of the crop tended to increase resulted from biological suppression by P. fluorescens P60, but not by T. harzianum nor T. koningii.